The Effect of Progressive Muscle Relaxation Therapy on Academic Stress Levels in Adolescents Class XII in Public Senior High School - Hanatasya Ridha Deanira; Hanim Nur Faizah; Miftahul Munir; Lukman Hakim; Dwi Maya Firdayanti; Rania Claudiasari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Academic stress is an individual's perception and assessment of what is perceived as an academic stressor related to science and education, this condition occurs due to a mismatch between academic demands and abilities of adolescents. This study aims to determine the effect of progressive muscle relaxation therapy on academic stress levels in adolescents of grade XII. The research design used in this study is Quantitative Pre-experimental: pre-post test (one group pre-post test design) with a cohort approach. The population in this study were all adolescents of grade XII Social C Public Senior High School 2 Tuban as many as 36 adolescents and grade XII Science 2 Public Senior High School 4 Tuban as many as 37 adolescents. The total participants of this study were about 73 adolescents selected by cluster random sampling technique obtained 31 adolescents each grade. Data were collected through pre-test and post-test questionnaires. The data was analyzed using the Wilcoxon test with a significance level of α <0.05 using SPSS software version 26 for windows, the results obtained were Asymp sig (2-tailed) = 0.000, which means the smaller the p-value, the more significant the results of the study, so that p = 0.000 <0.05 then H1 is accepted. This shows that progressive muscle relaxation therapy has an effect on reducing academic stress levels in grade XII adolescents at Public Senior High School.